2017
DOI: 10.1161/atvbaha.116.308461
|View full text |Cite
|
Sign up to set email alerts
|

Role of KCa3.1 Channels in Macrophage Polarization and Its Relevance in Atherosclerotic Plaque Instability

Abstract: Objective-Emerging evidence indicates that proinflammatory macrophage polarization imbalance plays a key role in atherosclerotic plaque progression and instability. The calcium-activated potassium channel KCa3.1 is critically involved in macrophage activation and function. However, the role of KCa3.1 in macrophage polarization is unknown. This study investigates the potential role of KCa3.1 in transcriptional regulation in macrophage polarization and its relationship to plaque instability. Approach and Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…Stott et al 46 showed that K V 7 channel-mediated relaxations in response to isoproterenol were dependent on exchange protein directly activated by cAMP in mesenteric artery but not in renal artery in rats, indicating that intermediate signaling steps from β-adrenoceptors to K V 7 channels vary depending on vascular beds. Xu et al 47 showed that blocking K Ca 3.1 channels reduced atherosclerotic burden and enhanced plaque stability in a mouse model of atherosclerosis by inhibiting macrophage differentiation toward proinflammatory M1 phenotype. However, nonspecific inhibition of K Ca 3.1 should require caution because it could lead to microvascular endothelial dysfunction by inhibiting EDH-mediated responses.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…Stott et al 46 showed that K V 7 channel-mediated relaxations in response to isoproterenol were dependent on exchange protein directly activated by cAMP in mesenteric artery but not in renal artery in rats, indicating that intermediate signaling steps from β-adrenoceptors to K V 7 channels vary depending on vascular beds. Xu et al 47 showed that blocking K Ca 3.1 channels reduced atherosclerotic burden and enhanced plaque stability in a mouse model of atherosclerosis by inhibiting macrophage differentiation toward proinflammatory M1 phenotype. However, nonspecific inhibition of K Ca 3.1 should require caution because it could lead to microvascular endothelial dysfunction by inhibiting EDH-mediated responses.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…M1 macrophages increase and sustain the ongoing inflammatory response by producing proinflammatory mediators . Persistent induction of M1 macrophages promotes an inflammatory state and causes tissue injury, which are associated with atherosclerosis progression and plaque rupture . In contrast, M2 macrophages have an antiatherogenic effect through inflammation resolution, tissue repair, and efferocytosis .…”
Section: Introductionmentioning
confidence: 99%
“…19 Persistent induction of M1 macrophages promotes an inflammatory state and causes tissue injury, which are associated with atherosclerosis progression and plaque rupture. 20,21 In contrast, M2 macrophages have an antiatherogenic effect through inflammation resolution, tissue repair, and efferocytosis. 19,22 Overall, macrophage foam cell formation and polarization are both fundamental contributors to the development and progression of atherosclerotic plaques.…”
mentioning
confidence: 99%
“…In human atherosclerotic plaques, markers for M1 and M2 macrophages are present in the early and advanced stages of plaque development (16,17). Previous studies in hypercholesterolemic mice have demonstrated that M2 macrophages reduce atherosclerosis, whereas suppression of M2 polarization enhances plaque progression (18)(19)(20). Therefore, it may be concluded that macrophage polarization is important for plaque progression in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%